Identifying Threshold Effects in Credit Risk Stress Testing - Mendez Morales, Armando (IMF Working Papers; Working Paper ;, 2004)
Using data from Argentina, Australia, Colombia, El Salvador, Peru, and the United States, we identify three types of threshold effects when assessing the impact of economic activity on nonperforming loans (NPLs). For advanced financial systems showing low NPLs, there is an embedded self-correcting adjustment when NPLs exceed a minimum threshold. For financial systems in emerging markets in Latin America showing higher NPLs, there is instead a magnifying effect once NPLs cross a (higher) threshold. GDP growth apparently affects NPLs only below a certain threshold, which is consistent with observed lower elasticity of credit risk to changes in economic activity in boom periods.